A facile and regioselective multicomponent synthesis of chiral aryl-1, 2-mercaptoamines in water followed by monoamine oxidase (MAO-N) enzymatic resolution. Issue 40 (4th October 2019) - Lauder, Kate; Masci, Domiziana; Toscani, Anita; Al Mekdad, Aya; Black, Gary W.; Brown, Nicola L.; Turner, Nicholas J.; Luisi, Renzo; Castagnolo, Daniele
Abstract : A microwave assisted multicomponent protocol on water allows the regioselective synthesis of chiral aryl-1, 2-mercaptoamines. The enzymatic resolution of the racemates leads to enantioenriched products. Abstract : A facile microwave assisted three-component protocol allows the synthesis of chiral aryl-1, 2-mercaptoamines in water in a few minutes with high yields, bypassing the use of toxic aziridine intermediates. The chiral 1, 2-mercaptoamines were then deracemized through enzymatic resolution of the racemates using monoamine oxidase (MAO-N) biocatalysts.